Can you see it? : an eye-opening adventure - Roller, Pam.; Young, Mike; Williams, Tara, 1973- ([Mahway, N.J.] : Troll Communications, 2002)
Contains fourteen picture puzzles.
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Puzzles; Puzzles